Intraluminal Thrombus has a selective Influence on Matrix Metalloproteinases and Their inhibitors (tissue inhibitors of Matrix Metalloproteinases) in the wall of Abdominal Aortic Aneurysms - Khan, J. A.; Abdul Rahman, Mohd Norhisham Azmi; Mazari, F. A. K.; Shahin, Y; Smith, G; Madden, L; Fagan, M. J.; Greenman, J; McCollum, P. T.; Chetter, I. C. (Elsevier, 2012)
Background: The influence of intraluminal thrombus (ILT) on the proteolytic environment within the wall of an abdominal aortic aneurysm (AAA) is unknown. This is the first study to examine the correlation between ILT thickness and the levels of matrix metalloproteinases (MMPs) and their natural inhibitors (tissue inhibitors of matrix metalloproteinases [TIMPs]) within the adjacent AAA wall. Methods: Thirty-five patients undergoing elective repair of AAAs were studied. A single full thickness infrarenal aortic sample was obtained uniformly from the arteriotomy site from each patient. All samples were snap frozen and analyzed for total and active MMP 2, 8, and 9 and TIMP 1 and 2. Thrombus thickness at the specimen site was measured on the preoperative contrast computed tomographic angiograms. Results: There was a statistically significant correlation between ILT thickness, concentration of TIMP 1, and active concentration of MMP 9. MMP 2 (active and total) and TIMP 2 demonstrated a positive correlation with ILT thickness, although not statistically significant. Conclusion: In this novel study, we found a significant positive correlation of ILT thickness with active MMP 9 and TIMP 1 concentration in the adjacent AAA wall, and this may have implications for AAA expansion and eventual rupture.